INERCJA ROCZNEGO ODPŁYWU CAŁKOWITEGO RZEK POLSKI WZGLĘDEM MIĘDZYROCZNEJ ZMIENNOŚCI PRZEBIEGU ELEMENTÓW KLIMATYCZNYCH - MARSZ, ANDRZEJ A.; STYSZYŃSKA, ANNA (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2021)
The work discusses the formation of the annual total runoff of Polish rivers as a function of changes in the annual values of climatic elements. The results of the analysis show that in the years 1966–2015, 40–50% of the runoff variance in a hydrological year was determined by the variability of climatic elements that occurred in the preceding year, and 20–30% in the same year. This indicates the occurrence of much stronger inertia in the variability of the runoff in relation to the variability of weather conditions. The main elements influencing the variability of the runoff are the annual rainfall and the annual air temperature in the preceding year, and in the same hydrological year – the variability of annual rainfall, sunshine duration and air temperature. The runoff from the area of Poland shows a strong relationship (R = 0.82) with the de Martonne climate aridity indices, the variability of which in the preceding and the current year together explains 66% of its variance.